2014
DOI: 10.1111/jdv.12850
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis in the elderly: epidemiological and clinical aspects, and evaluation of patients with very late onset psoriasis

Abstract: This study highlights phenotypic features of psoriasis in elderly and in very late onset psoriasis. The management of these fragile patients remains poorly codified and needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
55
3
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 16 publications
16
55
3
4
Order By: Relevance
“…We found also that the patients who have an occupation in contact with the public scored significantly higher, probably for the same reasons. Earlier studies also noted the decreasing impact of disease with age . It was confirmed herein.…”
Section: Clinical Data and Comparisons Of Discordant Groupssupporting
confidence: 87%
“…We found also that the patients who have an occupation in contact with the public scored significantly higher, probably for the same reasons. Earlier studies also noted the decreasing impact of disease with age . It was confirmed herein.…”
Section: Clinical Data and Comparisons Of Discordant Groupssupporting
confidence: 87%
“…A cross-sectional study including 2201 adults with psoriasis in France found that childhood onset of psoriasis was not associated with higher frequencies of large waist circumference, obesity, diabetes, dyslipidemia and hypertension; however, these outcomes were associated with increased age[7]. Another similar study investigating very late onset psoriasis (over age of 70) found that very late onset patients tended to have lower frequencies of obesity, diabetes, hypertension, and dyslipidemia than ‘early’ onset patients[8]. In our study, comorbidity prevalence did not increase or decrease with age as indicated in the previous study of psoriatic patients; this may be due to the inclusion of only moderate to severe patients, as metabolic diseases have been found to be more prevalent among these patients and more highly associated with systemic inflammation, these patients may have different distribution patterns of metabolic comorbidities than general patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have examined the association between childhood and very late onset psoriasis and metabolic and cardiovascular comorbidities[7,8]. Age at onset was not found to be an independent risk factor for comorbidities in patients with childhood onset psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…Bei etwa jedem dritten Patienten mit klassischer Psoriasis vulgaris treten auch intertriginöse Hautveränderun-gen auf. Bei Kindern und älteren Patienten tritt Psoriasis intertriginös etwas häu-figer auf [7,10]. Bei der Psoriasis inversa besteht eine vornehmliche Beteiligung der Beugeseiten der großen Gelenke (Ellenbeuge, Kniebeuge; [2,9,14]).…”
Section: Epidemiologieunclassified